Nonnus' paraphrase between poetry, rhetoric and theology : rewriting the fourth gospel in the fifth century - Ypsilanti, Maria; Franco, Laura (Mnemosyne, bibliotheca classica Batava. Supplementum, 2020)
"This book investigates the various paraphrastic techniques employed by Nonnus of Panopolis (5th century CE) for his poetic version of the Gospel of John. The authors look at Nonnus' Paraphrase, the only extant poetic Greek paraphrase of the New Testament, in the light of ancient rhetorical theory while also exploring its multi-faceted relationship with poetic tradition and the theological debates of its era. The study shows how interpretation, cardinal both in ancient literary criticism and in theology, is exploited in a poem that is exegetical both from a philological and a Christian point of view and adheres, at the same time, to the literary principles of Hellenistic times and late antiquity"--